Relationship between blood level chloroquine, metabolite desethylchloroquine and paracytaemia of Plasmodium falciparum infection in malaria endemic area Purworejo - Handayani, Rina; Prahasto, Iwan Dwi; Tjokrosonto, Soesanto (Indonesian Journal of Pharmacy, 2005)
Chloroquine is the drug of choice for Plasmodium falciparum and has long been used as the first line treatment in malaria in Indonesia. However, recent studies show that chloroquine resistance has been found in several endemic area. This study was aimed at investigating the correlation between whole blood chloroquine and desethylchloroquine levels and paracytaemia in the endemic areas.The study was carried out in Pituruh sub-district of Purworejo district. Thirty two subjects were enrolled using active case detection and passive case detection methods. Inclusion criteria: age 10-50 years old, asexual P falciparum > 1000/μl blood, not pregnant women, not having complication of malaria, willing to be observed for 28 days and agree to take part in study by signing an informed concent.The 32 samples were collected at day 2, and 10 samples were collected at 0, 2, 7, 14, 21, 28 days to detect the precence of paracytaemia and chloroquine and desetylchloroquine levels. A high Performance Liquid Chromatograph (HPLC) was used to analyze blood chloroquine and desethylchloroquine levels.The result show that chloroquine has been regurarly used (in 78.12% of subject) the day before the treatment was started. Mean blood redundant chloroquine and desethylchloroquine (combined) redundant in day 2 were 397.7 (SEM: 38.1) and prosentage of paracytaemia inhibitory effect was 93.7% (SEM: 2.07). This study observed no significant correlations between blood chloroquine and desethylchloroquine levels and paracytaemia.The result showed that increasing and decreasing of blood level chloroquine and desethylchloroquine has no correlation to the increasing or decreasing of paracytaemia inhibition in patients with Plasmodium falciparum infection in the endemic areas, which might be due to many factors including resistance to chloroquine.Key words : chloroquine, desethylchloroquine – P falciparum